The Impact of Professional Fiqh’s Teacher on Enhancing the Student’s Learning Achievement - Ayuni Hasibuan, Winda; Ritonga, Maisaroh; Ulya, Basyarul (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2024)
Research on the impact of Fiqh educators' professionalism on students' academic achievement is significant for investigation, it offers insights into how aspects expertise, classroom management, contribute to enhancing learning quality. The results may serve as a foundation for crafting more effective educational policies and training programs for educators to enhance their professionalism. This study aims to assess the impact of Fiqh teachers' professionalism on improving student learning outcomes in class X at MAS Islamiyah Subulussalam, Sumberjo District, Torgamba District, Labuhanbatu. The research employs a quantitative approach, utilizing the product-moment correlation technique to test the validity of the questionnaire.The results indicate that teacher professionalism in the teaching and learning process is satisfactory, as reflected by the percentage range of 56%-100%. Student learning achievement, based on the calculations, scores 7.7, falling within the range of 56%-100% according to the established standards. Data analysis reveals a correlation value of 0.829, which exceeds the critical value (rt). The validity test for the research instrument yielded a result of 0.538 at a 5% significance level. The influence observed is classified as high/strong, as indicated by an "rxy" value of 0.289, which corresponds to a strong effect, leading to the acceptance of the alternative hypothesis (Ha).